Extraction of Oxidative Enzymes from Green Tea Leaves and Optimization of Extraction Conditions. Issue 12 (3rd November 2020) - Koohi, Saleh; Nasernejad, Bahram; Zare, Masoud Habibi; Elahifard, Maryam; Shirazian, Saeed; Ghadiri, Mahdi
Abstract: Oxidative enzymes, polyphenol oxidase (PPO) and peroxidase (POD), were extracted from tea leaves and their activities were assessed. The Taguchi approach was used for the design, optimization, and statistical analysis of PPO and POD extraction. It was found that PPO and POD have the highest activity at an extraction temperature of 50 °C, at pH = 9 and 5 for PPO and POD, respectively, a buffer solution concentration of 0.05 M, a buffer solution/tea leaves ratio of 3, a contact time of 2 min, and in the presence of 6 % polyvinylpyrrolidone and 5 % Tween® 80. The highest activities were 0.380 and 0.022 U mL −1 for PPO and POD, respectively. Furthermore, PPO was completely inactivated after 30 min at 40 and 60 °C. In contrast, POD lost only 40 % of its activity after 30 min at 40 and 60 °C. Abstract : The Taguchi approach was used for the design, optimization, and statistical analysis of polyphenol oxidase (PPO) and peroxidase (POD) extraction. The order of importance of the parameters for PPO extraction was temperature > pH > addition of Tween® 80 while for POD it was pH > addition of a surfactant > temperature.